Information Technology Governance Assessment in Higher Education Institution Using COBIT 5 Framework - Helmi Naufal Rafdiansyah; Adhi Alfian; Zaldy Adrianto (Universitas Padjadjaran, 2022)
Information Technology (IT) is an essential part of overall organizational governance, and higher education is an educational institution that requires IT support. This study aims to evaluate how effective and efficient the implementation of information technology governance at the PTNBH X as measured by COBIT 5 Framework. This study will be an exploratory one that will rely on qualitative data. The domains Evaluate, Direct, and Monitoring (EDM) will be the focus of this study. Data collecting was the first stage of the study, followed by analysis of maturity and gap levels, analysis and problem-solving in the implementation of IT governance and recommendations, and finally conclusions and recommendations. According to the results of PTNBH X's capability level evaluation of the EDM domain, the company is at level 1 (performed process), with a value of 1.4. It means most of the EDM domains in PTNBH X implemented process achieves its process purpose, but not yet at the level that the process is being planned, monitored and adjusted to their needs.